Perbandingan Hasil Penilaian Ketebalan Korteks dengan Menggunakan Mental Index pada Pasien Wanita Berdasarkan Kelompok Umur 30-70 Tahun - Edward Perdana Putra; Sarianoferni; Endah Wahjuningsih (Denta Journal Kedokteran Gigi, 2015)
Background: The osteoporosis risk can be detected through the width of cortical mandible and porosity which can be seen in panoramic radiography. One of measurement methods using panoramic radiography in assessing the quality of bone and observing symptom of resorption and osteoporosis by utilizing Mental Index. Mental Index is a method in counting the average width of cortex under foramen mentale because thin mandible might correlates with decreasing of bone density. Purpose: To compare the assessment result of the cortex thickness by using Mental Index on women patient based on age of group (aged 30-70) at RSGM FKG Hang Tuah University, Surabaya. Materials and Methods: In this research, panoramic radiography of women patients aged 30 to 70 were used with utilizing radiomorfometri Mental Index to assess the mandibular cortical thickness manually using adigital caliper (accuracy of 0,01mm). Result: Based on One Way ANOVA assessment, p=0.000 value was found in which it means that there was a significant difference from the result of cortical thickness assessment in age of groups using Mental Index based onpanoramic radiography of women patients aged 30-70 at RSGM FKG Hang Tuah University, Surabaya. Conclusion: The assessment of cortical thickness by using Mental Index on women patients who experienced a decrease bone density in the age of 56-70 years old and which is compared with previous three groups of age, 30-35 years old, 36-45 years old and 46-55 years old and out of 93 panoramic radiographies, 11 panoramic radiographies were detected osteoporosis or the percentage of osteoporosis occurance based on Mental Index was 12%.